2011
DOI: 10.1016/j.bbadis.2011.02.012
|View full text |Cite
|
Sign up to set email alerts
|

ETS-domain transcription factor Elk-1 mediates neuronal survival: SMN as a potential target

Abstract: Elk-1 belongs to the ternary complex factors (TCFs) subfamily of the ETS domain proteins, and plays a critical role in the expression of immediate-early genes (IEGs) upon mitogen stimulation and activation of the mitogen-activated protein kinase (MAPK) cascade. The association of TCFs with serum response elements (SREs) on IEG promoters has been widely studied and a role for Elk-1 in promoting cell cycle entry has been determined. However, the presence of the ETS domain transcription factor Elk-1 in axons and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 40 publications
0
42
1
Order By: Relevance
“…The lifespan of 0.9% NaCl and 1% DMSO-treated mice (1.66 Ϯ 0.55 d) proved to be similar to 0.9% NaCl-treated mice (1.65 Ϯ 0.62 d; Biondi et al, 2010). Body weight and lifespan recordings were performed every day until the death of the animal.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The lifespan of 0.9% NaCl and 1% DMSO-treated mice (1.66 Ϯ 0.55 d) proved to be similar to 0.9% NaCl-treated mice (1.65 Ϯ 0.62 d; Biondi et al, 2010). Body weight and lifespan recordings were performed every day until the death of the animal.…”
Section: Methodsmentioning
confidence: 99%
“…Stimulation of the NMDA receptors was achieved by exposing cells to 100 M NMDA, as described previously (Biondi et al, 2010). To evaluate the CREB dependency, carbamoyl]-2-naphthyl dihydrogen phosphate) (10 M; Sigma) was added to the culture.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…clearly lowered SMN level; the latter was obviously related to the poor condition of the cells [37]. The continuing SMN expression at the absence of NF-κB in the nucleus suggests that the expression under these conditions is controlled by different transcription factor(s); it has been shown that SMN is a target gene also for Elk-1 [9] and CREB [24]. However, the functionality of the SMN protein complex-dependent motoneuron survival pathway is in serious doubt.…”
Section: Discussionmentioning
confidence: 99%